Pelatihan Pengelolaan Sampah Plastik di Dusun Sumber Rejo Desa Lembeyan Wetan Kabupaten Magetan - Nurhidayati, Maulida (Amalee: Indonesian Journal of Community Research and Engagement, 2020)
Sumber Rejo Hamlet is a hamlet located in Lembeyan Wetan Village with the majority of the population's livelihoods being farmers. Community empowerment was chosen as a step to increase community knowledge, skills and motivation to strengthen their resources. Using ABCD approach, the activity began with the mapping of the area, community, associations, and individual assets. There were a number of problems that occurred in Sumber Rejo Hamlet. In mapping step, several obstacles faced by the community especially the fact that there were the amount of garbage scattered in the river and the lack of management of plastic waste. Then, plastic waste management training program was chosen to run. This activity is becoming the focus of main activities because more and more plastic waste will potentially pollute the environment. The waste management training was held on August 7, 2019 at Mrs. Katini’s home, one of the residents in Sumber Rejo Hamlet. The target of this activity is homemakers in Sumber Rejo village with the aim that they become more concerned with plastic waste and its use. Presenters of plastic waste management training came from Kopma Al-Hikmah IAIN Ponorogo where the implementation of the training went very well. The participants were very enthusiastic in welcoming the training and were able to take part in the activity until the end. Keywords: empowerment, community, pollution, environment, garbage Abstrak Dusun Sumber Rejo adalah dusun yang terletak di Desa Lembeyan Wetan dengan mayoritas mata pencaharian penduduk adalah petani. Pemberdayaan masyarakat dipilih sebagai langkah untuk meningkatkan pengetahuan, keterampilan, dan motivasi masyarakat untuk memperkuat sumber daya mereka. Menggunakan pendekatan ABCD, kegiatan dimulai dengan pemetaan area, komunitas, asosiasi, dan aset individu. Ada sejumlah masalah yang terjadi di Dusun Sumber Rejo. Dalam langkah pemetaan, beberapa kendala yang dihadapi oleh masyarakat terutama fakta bahwa ada jumlah sampah yang berserakan di sungai dan kurangnya pengelolaan sampah plastik. Kemudian, program pelatihan pengelolaan limbah plastik dipilih untuk dijalankan. Kegiatan ini menjadi fokus kegiatan utama karena semakin banyak sampah plastik yang berpotensi mencemari lingkungan. Pelatihan pengelolaan sampah plastik diadakan pada 7 Agustus 2019 di rumah Ny. Katini, salah satu warga di Dusun Sumber Rejo. Sasaran dari kegiatan ini adalah para ibu rumah tangga di desa Sumber Rejo dengan tujuan agar mereka lebih peduli dengan sampah plastik dan penggunaannya. Penyaji pelatihan pengelolaan sampah plastik datang dari Kopma Al-Hikmah IAIN Ponorogo di mana pelaksanaan pelatihan berjalan dengan sangat baik. Para peserta sangat antusias dalam menyambut pelatihan dan dapat mengambil bagian dalam kegiatan sampai akhir. Kata kunci: pemberdayaan, masyarakat, pencemaran, lingkungan, sampah